2013
DOI: 10.1186/1471-2458-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor advertising, obesity, and soda consumption: a cross-sectional study

Abstract: BackgroundRecent research has shown that neighborhood characteristics are associated with obesity prevalence. While food advertising in periodicals and television has been linked to overweight and obesity, it is unknown whether outdoor advertising is related to obesity.MethodsTo test the association between outdoor food advertising and obesity, we analyzed telephone survey data on adults, aged 18–98, collected from 220 census tracts in Los Angeles and Louisiana. We linked self-reported information on BMI and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 37 publications
(39 reference statements)
4
59
1
2
Order By: Relevance
“…17 Although the patterns reported here may not generalize to all American cities, the results are consistent with other works showing disparities in outdoor obesity-related advertising found in Los Angeles, New Orleans, Philadelphia, Austin, and New York. 7,9,10 It is important to point out that the present study does not address the gap in the literature surrounding the causal link between unhealthy advertising and obesity and more work is needed in this area. Future research should also investigate the ways in which the broader food information environment, or macro environments, shapes food choice in much the same way that research has confirmed that micro environments, like interiors of restaurants and grocery stores, are designed to encourage unhealthy food choices and overeating.…”
Section: Resultsmentioning
confidence: 91%
“…17 Although the patterns reported here may not generalize to all American cities, the results are consistent with other works showing disparities in outdoor obesity-related advertising found in Los Angeles, New Orleans, Philadelphia, Austin, and New York. 7,9,10 It is important to point out that the present study does not address the gap in the literature surrounding the causal link between unhealthy advertising and obesity and more work is needed in this area. Future research should also investigate the ways in which the broader food information environment, or macro environments, shapes food choice in much the same way that research has confirmed that micro environments, like interiors of restaurants and grocery stores, are designed to encourage unhealthy food choices and overeating.…”
Section: Resultsmentioning
confidence: 91%
“…Lesser et al showed that for every 10% increase in outdoor food advertising, there was a 5% greater odds of being overweight or obese, controlling for other factors [20]. While some outdoor food advertising occurs on the exteriors of food stores [21] and restaurants [17]-raising the possibility that it is the presence of food sources that matters for behavior rather than the advertising itself-the Lesser et al study specifically excluded storefront ads [20], suggesting the particular and independent importance of other advertising in communities.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that 97.8% and 89.4% of food-product advertisements viewed by children 2-11 years old and adolescents 12-17 years old, respectively, marketed foods that were high in fat, sugar, or sodium (121). One study found that the higher the percentage of outdoor advertisements for beverages in a census tract, the greater the odds of obesity in its residents (88). According to the Federal Trade Commission in 2009, advertisers spent the most on marketing SSBs to teenagers (56,82).…”
Section: Limit Marketing Of Ssbs and Minimize Marketing's Impact On Cmentioning
confidence: 99%